The Effect of Harmonization of International Trade Regulations on the National Rule of Law - anggraini, sahwa desma (Ipso Jure, 2025)
Globalization has changed the dynamics of international trade, strengthening global economic integration through organizations such as the WTO and trade agreements such as the RCEP. Harmonization of international trade regulations aims to create global market stability by harmonizing national and international regulations. However, major challenges arise for developing countries, including Indonesia, in maintaining the sovereignty of national law without neglecting international obligations. In this context, Indonesia faces dilemmas related to protectionist policies, such as restrictions on nickel ore exports and restrictions on horticultural imports, which often clash with WTO rules. This study aims to analyze the impact of harmonization of international trade regulations on Indonesia's national legal sovereignty and identify strategies that can be applied to overcome these challenges. Using normative juridical methods and case studies, this study explores the tension between domestic policy and international obligations. The results of the study show that the alignment between the Trade Law and international rules, as well as the adoption of a legal flexibility approach, can be a solution to balance national interests with global obligations. This research provides strategic recommendations for the Indonesian government in formulating trade policies that can strengthen the country's position in the global market without sacrificing domestic interests.